2019
DOI: 10.3389/fimmu.2019.02237
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Low-To-Medium-Affinity Fcγ Receptors: Functional Consequences, Disease Associations, and Opportunities for Personalized Medicine

Abstract: Fc-gamma receptors (FcγR) are the cellular receptors for Immunoglobulin G (IgG). Upon binding of complexed IgG, FcγRs can trigger various cellular immune effector functions, thereby linking the adaptive and innate immune systems. In humans, six classic FcγRs are known: one high-affinity receptor (FcγRI) and five low-to-medium-affinity FcγRs (FcγRIIA, -B and -C, FcγRIIIA and -B). In this review we describe the five genes encoding the low-to-medium -affinity FcγRs (FCGR2A, FCGR2B, FCGR2C, FCGR3A, and FCGR3B), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 189 publications
(280 reference statements)
3
69
0
3
Order By: Relevance
“…- 13 -Monocytes and monocyte subsets can also be identified based on CD14 expression (discussed in Section 1.1.1), a cell surface co-receptor for LPS [23,95], and whether they express Fc-gamma receptor IIIa (CD16a); see Section 1.2.3 for further subset definitions. CD16a (FcγRIIIA) consists of (i) two extracellular Ig-like domains that bind to IgG, (ii) a transmembrane domain that associates with adaptor proteins containing an immunoreceptor tyrosine-based activating motif (ITAM) and induces downstream intracellular signalling, and finally, (iii) a short intracellular domain [96]. CD16a associated γ-chains are essential for signalling and stable expression, as well as targeting the receptor on the monocyte cell membrane [96].…”
Section: The Monocyte System and Its Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…- 13 -Monocytes and monocyte subsets can also be identified based on CD14 expression (discussed in Section 1.1.1), a cell surface co-receptor for LPS [23,95], and whether they express Fc-gamma receptor IIIa (CD16a); see Section 1.2.3 for further subset definitions. CD16a (FcγRIIIA) consists of (i) two extracellular Ig-like domains that bind to IgG, (ii) a transmembrane domain that associates with adaptor proteins containing an immunoreceptor tyrosine-based activating motif (ITAM) and induces downstream intracellular signalling, and finally, (iii) a short intracellular domain [96]. CD16a associated γ-chains are essential for signalling and stable expression, as well as targeting the receptor on the monocyte cell membrane [96].…”
Section: The Monocyte System and Its Heterogeneitymentioning
confidence: 99%
“…CD16a (FcγRIIIA) consists of (i) two extracellular Ig-like domains that bind to IgG, (ii) a transmembrane domain that associates with adaptor proteins containing an immunoreceptor tyrosine-based activating motif (ITAM) and induces downstream intracellular signalling, and finally, (iii) a short intracellular domain [96]. CD16a associated γ-chains are essential for signalling and stable expression, as well as targeting the receptor on the monocyte cell membrane [96]. Humans seem to express two FcγRIIIa (CD16a) allotypes that differ in a single amino acid residue at position 158;…”
Section: The Monocyte System and Its Heterogeneitymentioning
confidence: 99%
“…Genetic variation in Fcγ receptors can result in functional changes including differing affinities of FcγR for Ig or different FcγR expression levels (reviewed by Nagelkerke et al ) and can influence how antibodies toward malaria antigens interact with immune cells expressing these receptors . While clinical significance is not always established, in Asian and African populations a prevalent FcγRIIB mutation has likely been selected for by malaria and a variation in FcγRIIA appears to protect against clinical malaria …”
Section: Functional Antibody In Malariamentioning
confidence: 99%
“…Studies showed such genetic variations affecting immune functions, increasing individual's susceptibility and impacting therapeutical response of disorders/diseases [50][51][52]. Studies also showed that there are many different kinds of disorders/ disease linked with such genetic variations associated dysfunctions of FcRs (gain or loss) with different consequences occurring with heterogeneity among different ethnic groups [53][54][55]. [66].…”
Section: Genetic Variation Of Fcγrsmentioning
confidence: 99%